Dampak Green Attitude, Green Satisfaction, Green Purchase Intention terhadap Green Loyality (Studi pada Konsumen EIGER Adventure Store Sidoarjo) - Indriyani, Risa; Yani, Muhammad; Nugroho, Tofan Tri (Ekonomis: Journal of Economics and Business, 2025)
This study aims to examine the effect of green attitude, green satisfaction, and green purchase intention on green loyalty among visitors to the Eiger Adventure Store Sidoarjo. The data analysis method used is quantitative with a causality approach between variables through hypothesis testing. The population of this study was all visitors who shopped at the Eiger Adventure Store Sidoarjo, with a sampling technique using a non-probability sampling method with a random sampling technique. The results showed that green attitude, green satisfaction, and green purchase intention significantly had a positive effect on green loyalty. This shows that the higher the green attitude, green satisfaction, and green purchase intention, the higher the level of green loyalty owned by consumers. The implication of this study is the importance of companies to pay attention to these aspects in an effort to build and maintain consumer loyalty to environmentally friendly products or brands.